2019
DOI: 10.1155/2019/2528490
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of the Antibacterial Efficiency of Silver Nanoparticles against Gram-Positive and Gram-Negative Bacteria Using Blue Laser Light

Abstract: Silver nanoparticles (Ag-NPs) possess excellent antibacterial properties and are considered to be an alternative material for treating antibiotic-resistant bacteria. The present study was aimed at enhancing the antibacterial efficiency of Ag-NPs using visible laser light against Escherichia coli and Staphylococcus aureus in vitro. Four concentrations of Ag-NPs (12.5, 25, 50, and 100 μg/ml), synthesized by the chemical reduction method, were utilized to conduct the antibacterial activity of prepared Ag-NPs. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(32 citation statements)
references
References 34 publications
2
23
2
Order By: Relevance
“…Studies have shown that Gram-positive bacteria are more susceptible to AgNPs, compared to Gramnegative bacteria due to their structural differences. Contradicting earlier findings [38,39], we found no biased antibacterial action against either Gram-positive or Gramnegative bacteria, which could be attributed to the charge difference between the AgNPs and bacterial cells [32].…”
Section: Discussioncontrasting
confidence: 48%
“…Studies have shown that Gram-positive bacteria are more susceptible to AgNPs, compared to Gramnegative bacteria due to their structural differences. Contradicting earlier findings [38,39], we found no biased antibacterial action against either Gram-positive or Gramnegative bacteria, which could be attributed to the charge difference between the AgNPs and bacterial cells [32].…”
Section: Discussioncontrasting
confidence: 48%
“…The intensity of the fluorescence signal is proportional to the amount of ROS [ 28 ]. The research data obtained from previous reports suggest that: treatment with AgNPs alone did not induce significant ROS formation [ 29 ]; a significant increase in the DCF fluorescence intensity was observed for AgNP-treated bacterial cells [ 30 ]; colloidal silver significantly increased the production of ROS when compared with untreated cells [ 31 ]; ROS played a very important role in the antibacterial mechanism of AgNPs [ 32 ]. Interestingly, ROS detection data in AgNP-treated E. coli [ 33 ] showed that the fluorescence signal of AgNP-treated cells is lower than for the non-treated cells, for most treatment concentrations.…”
Section: Introductionmentioning
confidence: 99%
“…As in the case of the Gram-positive bacteria, this structural particularity prevents the action of Ag-NPs rendering acid-fast and gram-positive bacteria more resistance to the antimicrobial activity of Ag-NPs comparatively with Gram-positive bacteria. 143,144 For example, the Grampositive Bacillus subtilis, have a cell wall of 55.4 nm, the acid-fast M tuberculosis a 20.2 nm 145 while the Gramnegative Pseudomonas aeruginosa, has a cell wall of only a 2.4 nm. 146 Interestingly, although there are important functional differences between the mycobacteria cell wall and gram-positive bacteria, the DNA-based molecular taxonomy of bacteria based on the high similarity to genes, groups the classical acid fast-mycobacteria as gram-positive bacteria.…”
Section: Antibacterial Effect and Mechanism Of Silver Nanoparticlesmentioning
confidence: 99%
“…Additionally to the wall thickness and structure, the difference in resistance of different classes of bacteria can be explained by the fact that due to the high-presence of LPS the cell wall, Gram-negative bacteria has a higher negative charge, which promotes local adhesion and membraneclustering of particles and finally enhances the antibacterial effect of Ag-NPs. 144,162,163 Therefore, electrostatic interaction between bacterial cells (charged negatively) and AgNPs (charged positively) is critical for the antibacterial activity of NPs. 144,161,164 Moreover, to the above-mentioned action against the bacterial wall, AgNPs have the ability to enter inside bacteria's cytosol, to form cytoplasmic precipitates and to disrupt several bacterial-physiological processes.…”
Section: Antibacterial Effect and Mechanism Of Silver Nanoparticlesmentioning
confidence: 99%
See 1 more Smart Citation